Pengaruh Struktur Kepemilikan Dan Tata Kelola Perus-ahaan Terhadap Kualitas Audit - Mukti, Drajad Dwihadijaya; Hariadi, Bambang (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to determine the effect of ownership structure and corporate governance on the audit quality of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. The data include 260 companies’ Annual Reports collected through documentation with the purposive sampling method and analyzed by multiple regression utilizing SPSS 26 software. This study employs AQMS (Audit Quality Metric Score) to measure audit quality and a survey based on Hermawan (2009) to measure the Board of Commissioners and Audit Committee. The analysis results revealed the positive effect of the entrenchment effect, alignment effect, Board of Commissioners, Audit Committee, and independence of the Board on audit quality. In addition, the size of the Board of Directors and CEO duality had no significant effect on audit quality.